Determination of Lead in Whole Blood of Tattooed People Using Graphite Furnace -Atomic Absorption Spectrometry (GFAAS) (Latakia University Journal -Basic Sciences Series, 2019)
Lead toxicity has been one of the most significant health problems, that received considerable attention. The toxic effect of lead on human beings is well documented in interferes with a number of body functions most notably the central nervous system, the hematopoietic system and the kidney. The determination of lead levels in whole blood is one of the most useful diagnostic tests. The clinical standard procedure for the measurement of lead in whole blood is very simple and is based on the use of highly sensitive technique such as Graphite Furnace -  Atomic Absorption Spectrometer (GFAAS).The concentration of lead in blood is considered to be harmful to 10µg/dl four Adults and to 5µg/dl for children's.Study of (31) blood samples of tattooed people in Latakia city has showed a significant rise of lead in these specimens far exceed the permitted safe limits, and indicated that the concentration of lead in the blood sample is directly proportional to the area of the tattoo and inversely proportional to the age of the tattoo.